Efficient engineered probiotics using synthetic biology approaches: A review. (3rd October 2019) - Yadav, Monika; Shukla, Pratyoosh
Abstract: The uses of probiotics‐based food supplements are getting emphasis due to their power to ensure better health conditions. Probiotics have diverse and significant applications in the health sector, so probiotic strains require an understanding of the genome level organizations. Probiotics elucidate various functional parameters that control their metabolic functions. In this review, we have compiled aspects of synthetic biology, which are used for the optimization of metabolic processes in probiotics for their use as a supplement in allopathic medicines. Synthetic biology approaches provide information about diverse biosynthetic pathways and also facilitate the novel metabolic engineering approaches for probiotics strain improvement. We have discussed the synthetic biology approaches for producing engineered probiotics via genetic circuits, expression systems, and genome editing tools like CRISPR–Cas and PEVLAB. This review also enlightens future challenges in the development of engineered probiotics.